BRINGING TOGETHER DUAL-GENERALIZED COMPLEX NUMBERS AND DUAL QUATERNIONS VIA FIBONACCI AND LUCAS NUMBERS - Gurses, Nurten (UNIV POLITEHNICA BUCHAREST, SCI BULL, 2021)
In this study, the main target is to construct a bridge between dual quaternions and dual-generalized complex numbers via Fibonacci and Lucas numbers for p is an element of R. For this purpose, the algebraic structures and the well-known recurrence relations are investigated. Different matrix representations are improved, and examples are presented.
Keywords: Dual quaternion; Dual-generalized complex number; Fibonacci number; Lucas number; Mathematics; Physics